Komunikasi Visual Dalam Pemasaran Produk Industri Kreatif - Muhammad Sidqi Hawari; Eko Purwanto (Universitas Merdeka Malang, 2025)
In the digital era, visual communication has become an important element in the marketing of creative industry products, functioning to build brand identity and influence consumer purchasing decisions. This study aims to analyze the role of visual communication in increasing marketing effectiveness. The method used is a qualitative approach with literature studies, collecting data from various academic sources and relevant reports. The results of the study indicate that visual elements such as consistent color, typography, and illustration can increase consumer appeal and engagement. These findings provide a significant contribution to the understanding of effective visual communication strategies in the context of marketing. In conclusion, this study recommends that creative industry players consider cultural and psychological aspects in visual design to increase the relevance and impact of marketing in the future.